The maturing concept of estimating project cost contingency: A review - Baccarini, David (University of Technology, Sydney, 2006)
Contingency is a ubiquitous component of project cost estimating. This paper provides a review of the literature pertaining to the estimating of project cost contingency. It describes the flaws of the tradition percentage method for estimating project cost contingency and sets out more robust estimation methods - regression analysis, Monte Carlo simulation and artificial neutral networks. In particular, the application of regression analysis for predicting project cost contingency is reviewed in detail as a prelude to the author’s research into the development and testing of a regression model for forecasting project cost contingency for engineering construction projects.